La promotion d’une idéologie carolingienne autour de la reine Gerberge (milieu duXe siècle) - Justine Audebrand (Genre & Histoire)
Queen Gerberga, wife of King Louis IV (939-954) and mother of King Lothar (954-986), was at the heart of struggles for power that agitated Frankish and Germanic kingdoms in the mid tenth century. As the sister of the powerful Otto I, she was well placed to judge the balance of power between Otto and the Carolingians, and she began to construct, in collaboration with Bishop Rorico of Laon, a discourse aimed to counteract Ottonian supremacy. This discourse can be detected in a group of texts written in Rorico’s circle, some of which were dedicated to Gerberga. These texts developed a new form of female sainthood for the queen through the figure of Saint Clotild, at once queen, mother, and wife. These texts also sought to recover the idea of translatio imperii for the benefit of Carolingian kings, designated as legitimate heirs to the Romans and the Merovingian kings, unlike the Ottonian kings. This can be seen as a form of ideological competition with Ottonians, which was not, however, enought to stop the Carolingian decline and the recovery of the imperial title by Otto I in 962.